2014
DOI: 10.1371/journal.pone.0106228
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics of Aphids on Cereals: Digging in the Time-Series Data to Reveal Population Regulation Caused by Temperature

Abstract: Aphid populations show periodic fluctuations and many causes are attributed to their dynamic. We investigated the regulation by temperature of the aphid populations composed of Metopolophium dirhodum, Sitobion avenae, and Rhopalosiphum padi on winter wheat using a 24 years long time series data. We computed the sum of daily temperatures above 5°C, the threshold temperature for aphid development, and the sum of daily temperatures within the [0(threshold for wheat development),5] °C interval. Applying Generalise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 59 publications
(62 reference statements)
0
32
0
1
Order By: Relevance
“…Temperature is also another dominant abiotic factor. For aphids temperature has been shown to be a reliable indicator of future population growth (Brabec et al, 2014;Finlay & Luck, 2011). Mild temperatures, 18-25 °C, and rain shortages create conditions that are ideal for aphid reproduction and development (Gassen, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Temperature is also another dominant abiotic factor. For aphids temperature has been shown to be a reliable indicator of future population growth (Brabec et al, 2014;Finlay & Luck, 2011). Mild temperatures, 18-25 °C, and rain shortages create conditions that are ideal for aphid reproduction and development (Gassen, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…where: x s -standardised value of mean aphid abundance in a particular replicate; x o -experimental value of aphid abundance in a particular replicate; x a -average; s x -standard deviation of the aphid abundance values on all replicates together (Hendl 2009) Standardisation compensated for the important annual variation in aphid abundance (Wetzel 2004;Brabec et al 2014), which would conceal cultivar differences. The standardised values (x s ) were regressed on flowering time as a proxy for the cultivar-specific length of vegetation period, using second-order polynomial regression y = a + bx s + cx s 2 .…”
Section: Cultivarsmentioning
confidence: 99%
“…The maximum number of aphids on a crop stand (population peak) is determined by three population parameters: (i) initial number of immigrants, (ii) rate of population increase, which is determined by female developmental time and fecundity, and (iii) duration of the period of population increase, which is the time elapsed from immigration to the population peak (Honek 1991c;Honek et al 2006). The effects of immigrant numbers (Basky & Harrington 2000;Klueken et al 2009) and of factors determining the population growth rate, host plant quality (Honek 1991b;Honek & Martinkova 2004b), temperature (Dean 1974;Brabec et al 2014), aphid reproduction rate (Simon et al 1991;Sengonca et al 1994), and presence of natural enemies (Leslie et al 2009;Kerzicnik et al 2010) are well studied. In contrast, factors that determine the duration of the period of aphid population increase have not been sufficiently addressed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Munyuli (2009) reported that in comparison with control treatments, biological control of A. craccivora with predators increased yields by up to 66% for cowpea Vigna unguiculata (Linnaeus) Walp. Aphid populations can show periodic fluctuations (Brabec et al 2014). The population dynamics of aphids can be affected by seasonal changes in weather conditions, physiological characteristics of the host plant, farming methods, and management practices (Sequeira and Dixon 1997).…”
mentioning
confidence: 99%